Prevalence of raised IgE levels and absolute eosinophil count in bronchiolitis in children aged 2 months-2 years in tertiary care hospital - Krishnan, Elango; Periyasamy, Raja; Bharathi, Sindhu (International Journal of Research in Medical Sciences, 2016)
Background: Bronchiolitis is defined by IAP as ’A constellation of clinical symptoms and signs including viral upper respiratory prodrome followed by increased respiratory effort and wheeze in less than 2 year old children’. Aim of the study was to study the prevalence of raised IgE levels and raised Absolute eosinophil count & RSV (respiratory syncytial virus) antigen by PCR in bronchiolitis between age group of 2 months - 2 years with the occurrence of wheeze after first episode in 1 year follow up. Methods: 96 Children between 2 months - 2 years with first episode of bronchiolitis are included with the exclusion criteria of previous heart disease, lung disease, immune deficiency, second episode of bronchiolitis. In all the children CRP (C reactive protein), IgE (Immunoglobulin E), AEC (Absolute eosinophil count), RSV, PCR was done. Results: Out of 96 children, 60 children (62%) are males with maximum incidence on subjects of 53 (55.2%) in age group 2-6months. Fever, cough and rhinorrhoea are the major presenting complaints apart from breathlessness. Among 96 children 37 children (38.5%) had high serum IgE out of which 17 developed wheeze in 1 year of follow up. 27 (28.2%) had raisedAEC, out of which 10 had wheeze in follow up. Out of 10 children who had raised IgE andAEC, 3 had wheeze on follow up. 34 (35.4%) children had positive RSVPCR, 14 children had wheeze in follow up. Conclusions: The prevalence of raised IgE, AEC and RSV PCR are 38.5%, 28.1% and 41.1% and the occurrence of wheeze on follow up was 45.9%, 37% and 41.1% respectively.